GP207 A pain in the neck; a completed audit of use of throat cultures in a paediatric emergency department. (June 2019) - Geraghty, Jennifer; Caulfield, Fionnuala; Cormack, Maeve Mc
Abstract : Background: The National Institute for Clinical Excellence (NICE) published an innovation briefing on 'point-of-care diagnostic testing for suspected strep A infection in sore throat' in May 2018. This suggested that use of these tests in additional to clinical scoring systems could assist in rapid decision making, reduce unnecessary antibiotic use and provide additional patient reassurance compared with throat culture. Aims: To audit use of throat culture and rate of positive results in the paediatric emergency department of a secondary paediatric hospital. To raise awareness of the importance of using clinical scoring systems in assessing the need for throat culture. To identify whether the introduction of point of care testing for Group A streptococcal infection (GAS) would be feasible in this setting. Methods: Emergency department records were used to retrospectively identify patients with acute sore throat who had a throat culture taken over a three month period. This was followed by interventions in the form of education sessions and visual reminders placed in the emergency department on the modified centor criteria clinical scoring system for GAS. We then re-audited throat cultures taken over a one month period. Results: In the initial three month audit period 53 throat cultures were taken. Of these one (1.8%) was positive for GAS. Following the interventions 31 throat cultures were taken in the one month period of which four (12.9%) were positive for GAS. Conclusion: Throat cultures were used in the assessment of children with acute sore throat despite their limited assistance in clinical decision making in the emergency department setting. There was a very low yield of positive throat culture results in these patients. Raised awareness of clinical scoring systems did increase the yield of positive throat culture results. Further interventions are needed to reduce the rate of negative throat cultures before the benefit of introducing rapid antigen tests can be assessed.